Critical Thinking and Self Learning Skills in Mathematics Learning Outcomes - Rambe, Juli Asmida; Erika, Erika (Education Achievement: Journal of Science and Research, 2023)
The purpose of this study is to determine the relationship of ability critical thinking and self-regulated learning with learning outcomes of Mathematic Student Class V State Elementary School City of Medan, the number of students as many as 153 students. The technique used to analyze the data is the statistical technique of regression and correlation.The research result showed that there was a positive correlation between (1) Critical thinking and Mathematics learning outcomes (2) Self-regulated learning Mathematics learning outcomes (3) Critical thinking, Self-regulated learning and Mathematics learning outcomes. It can be concluded there is relationship between critical thinking, self-regulated learning and Mathematics learning outcomes.